OP0076 Kidneys of autoimmune nzb/w mice contain long-lived pc. (1st June 2001) - Radbruch, AH; Cassese, G; Lindenau, S; De Boer, B; Arce, S; Hauser, A; Riemekasten, G; Berek, C; Hiepe, F; Manz, RA
Abstract : Background: NZB/W mice develop a disease similar to human systemic lupus erythematosus (SLE), including autoantibody production, hypergammaglobulinaemia and inflammation of the kidneys. Large numbers of lymphocytes infiltrate the kidneys of these mice but the role of this organ for the production of antibodies is not clear. Objectives: Here, we compare the role of bone marrow, spleen and inflamed kidneys of NZB/W mice for the activation of B cells and for the persistence of antibody secreting cells (ASC). Methods: NZB/W mice were immunised i.p.i with Ovalbumin and then boosted 1 month later. The number of antigen-specific PC present in spleen, bone marrow and kidneys was determined by Elispot. The frequency of different cell types was determined by flow-cytometry. The distribution of PC in the different organs was investigated by microscopy. Results: ASC are present in the kidneys of mice with full blown disease, as many as in the spleen and bone marrow, and 50 times more than in the kidneys of normal mice. In the kidneys, ASC are located mainly in the outer medulla, close to B- and T cell infiltrates. The specificity of the ASC in the inflamed kidneys is not restricted to self-antigens. After immunisation of NZB/W mice with Ovalbumin (OVA), the antigen-specific ASC are found initially exclusively in the spleen. Weeks later, during a period of at least 3 month, OVA-specific ASC are found in stable and high numbers within the bone marrow and the kidneys of these mice, but no longer in the spleen. As determined by FACS, B cells with a germinal centre phenotype (B220+/PNA+) are found only in very low numbers in the kidneys, but in high numbers in the spleen of NZB/W mice. Germinal centres could not be detected in the kidneys, but in the spleen. The lack of B cell activation and the kinetics of the appearance of OVA-specific ASC in the kidneys suggest that in autoimmune NZB/W mice, plasma cells generated during an immune reaction in secondary lymphoid organs, later accumulate and persist in the inflamed kidneys, like in bone marrow. Conclusion: These experiments identify the inflamed kidneys of NZB/W mice as site of prime relevance for the homeostasis of plasma cells, irrespective of their specificity.